2016
DOI: 10.17795/ijcp-5452
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Ovarian Cancer Incidence in Iran

Abstract: Background: Cancer is a major cause of morbidity and mortality, among which ovarian cancer has a high incidence and case fatality. Gaining insight into the epidemiology and trends of ovarian cancer can be very influential in cancer screening and treatments programming. This study aimed to investigate the trends in the incidence of ovarian cancer in Iran, because this issue has been neglected so far.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…They decided that the system could be a good investigative tool that could improve communiqué between clinician as well as radiologist besides so assist procedure of decision making. They optional for planning potential revisions for obtaining additional decisive consequences in this field 14 .…”
Section: Resultsmentioning
confidence: 99%
“…They decided that the system could be a good investigative tool that could improve communiqué between clinician as well as radiologist besides so assist procedure of decision making. They optional for planning potential revisions for obtaining additional decisive consequences in this field 14 .…”
Section: Resultsmentioning
confidence: 99%
“…The investigation showed that Isfahan province has one of the highest ovarian cancer incidences in the country. [ 17 18 19 ] Relative risk estimation of uterine cancer seems to be the same in all cities. However, no studies have been done to assess incidence rates or risk of this disease in this province.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, obesity, smoking, inactivity, inappropriate nutrition, early menarche, and late menopause were known as the risk factors of ovarian cancer. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the incidence of many cancers, especially CRC, varies depending on the geographical situation of the area and has its own spatial pattern (20)(21)(22)(23)(24). Usually, Poisson regression is employed as the model for studying the correlation between variables at the level of a geographical unit with an outcome that is count.…”
Section: Introductionmentioning
confidence: 99%